Allogeneic mesenchymal stromal cells: Novel therapeutic option for mutated FLNA‐associated respiratory failure in the pediatric setting. Issue 1 (29th August 2019) - Pelizzo, Gloria; Avanzini, Maria A.; Lenta, Elisa; Mantelli, Melissa; Croce, Stefania; Catenacci, Laura; Acquafredda, Gloria; Ferraro, Aurelio L.; Giambanco, Caterina; D'Amelio, Lucia; Giordano, Salvatore; Re, Giuseppe; et al.
Abstract: Background: Mesenchymal stromal cell (MSC)‐mediated therapeutic effects have been observed in the treatment of lung diseases. For the first time, this treatment was used as rescue therapy in a pediatric patient with a life‐threatening respiratory syndrome associated with the filamin A ( FLNA ) gene mutation. Methods: A child with a new pathogenic variant of the FLNA gene c.7391_7403del (p.Val2464AlafsTer5), at the age of 18 months, due to serious and irreversible chronic respiratory failure, was treated with repeated intravenous infusions of allogeneic bone marrow (BM)‐MSCs. The child's respiratory condition was monitored. Immunologic studies before each MSC treatment were performed. Results: No acute adverse events related to the MSC infusions were observed. After the second infusion, the child's respiratory condition progressively improved, with reduced necessity for mechanical ventilation support. A thorax computed tomography (CT) scan showed bilateral recovery of the basal parenchyma, anatomical‐functional alignment and aerial penetration improvement. After the first MSC administration, an increase in Th17 and FoxP3 + T percentages in the peripheral blood was observed. After the second MSC infusion, a significant rise in the Treg/Th17 ratio was noted, as well as an increased percentage of CD20 + /CD19 + B lymphocytes and augmented PHA‐induced proliferation. Discussion: MSC infusions are a promising therapeutic modality for patients in respiratory failure, as observed in this pediatric patient with an FLNA mutation. MSCs may have an immunomodulatory effect and thus mitigate lung injury; although in this case, MSC antimicrobial effects may have synergistically impacted the clinical improvements. Further investigations are planned to establish the safety and efficacy of this treatment option for interstitial lung diseases in children.